Answer:
28/9
Step-by-step explanation:
If the roots are J and K, then:
3 (x − J) (x − K) = 0
3 (x² − (J+K)x + JK) = 0
So if we factor out the leading coefficient:
3x² − 2x − 4 = 0
3(x² − 2/3x − 4/3) = 0
The coefficient of the second term is the sum of the roots:
J + K = 2/3
And the constant is the product of the roots:
JK = -4/3
If we take the sum of the roots and square it:
(J + K)² = (2/3)²
J² + 2JK + K² = 4/9
And subtract twice the product:
J² + K² = 4/9 − 2JK
J² + K² = 4/9 − 2(-4/3)
J² + K² = 4/9 + 8/3
J² + k² = 28/9
For this case we have the following inequality:
3y - 2x> 8
The first thing we should do is to graph the function.
Then, see the set of points that are the solution of the inequality.
The solution set is given by the shaded region.
See attached image.
Answer:
Shaded region.
See attached image.
Answer:
w = x/50% = x/50/100
Step-by-step explanation:
We would turn the above question into an algebraic expression using variables.
To make a sugar syrup, we need sugar and water to form the solution.
Amount of sugar = x gram
Let amount of water = w gram
Sugar syrup solution = 50%
Sugar syrup solution = (amount of sugar)/(amount of water) × 100
50% = x/w × 100%
50% = x/w
Making w subject formula
w = x/50%
w = x/50/100